Roles and regulation of δ-catenin in tumorigenesis and neuronal diseases - Zhang, Yang; Xie, Keping; Jiang, Tingting (Frontiers in Cell and Developmental Biology, 2025)
CTNND2 gene is located on the short arm of human chromosome 5 and encodes δ-catenin protein, which interacts with different proteins and plays different cell functions. Studies have demonstrated that δ-catenin plays an important role in regulating synaptic maturation and neuronal integrity. The CTNND2 gene is closely associated with a variety of neurological diseases, including Cri-du-Chat syndrome, Autism spectrum disorders, Alzheimer’s disease, and Epilepsy. Furthermore, an increasing number of studies have demonstrated that CTNND2 is involved in various cancers and may serve as a novel biomarker for the diagnosis and treatment for these diseases. In this review, we will focus on the signaling regulatory functions of CTNND2 and its encoded protein δ-catenin in neuro-related diseases and cancers, and discuss the limitations of previous investigative studies and the challenges of the future researches on CTNND2 and δ-catenin signaling.